"Actinomyces ihumii, " a new bacterial species isolated from the digestive microbiota of a HIV-infected patient. (July 2016) - Ndongo, S.; Khelaifia, S.; Bittar, F.; Fournier, P.-E.; Raoult, D.
Abstract: We report the main properties of " Actinomyces ihumii " strain SD1 (= CSUR P2006) isolated from the stool of a 50-year-old HIV-infected man.